The Effect of a Matching Game on Elementary School Students Knowledge and Attitudes toward Clean and Healthy Living Behavior - Sahrir Ramadhan; Cembun; Nisrina (Indonesian Journal Publisher, 2026)
Background: Clean and Healthy Living Behavior (PHBS) should be introduced from elementary school age because poor PHBS implementation may increase the risk of environment-related diseases. A preliminary study at SDN 3 Rarang showed that students rarely received PHBS education and some students still did not wash their hands with soap and disposed of waste improperly. Purpose: This study aimed to determine the effect of health education through a matching game on students' knowledge and attitudes regarding PHBS. MethodsThis study used a pre-experimental design with a one-group pretest-posttest approach. The population consisted of 64 fourth- and fifth-grade students at SDN 3 Rarang, and 39 respondents were selected using proportional random sampling. The intervention was conducted on February 14, 2026, through health education and a card-matching game focusing on handwashing and proper waste disposal indicators. Data were collected using knowledge and attitude questionnaires and analyzed using the Wilcoxon Signed Rank Test. Results: Handwashing knowledge improved from mostly poor (87.2%) to sufficient (64.1%) and good (35.9%). Knowledge of proper waste disposal improved from mostly sufficient (48.7%) to good (94.9%). Positive attitudes toward handwashing increased from 33.3% to 53.8%, while positive attitudes toward proper waste disposal increased from 41.0% to 64.1%. The Wilcoxon test showed p < 0.001 for all variables. Conclusion Health education through a matching game influenced students' knowledge and attitudes regarding PHBS and may be recommended as an educational medium in school health programs.